Coconut matting bezoar identified by a combined analytical approach. Issue 2 (February 1986) - Levison, D A; Crocker, P R; Boxall, T A; Randall, K J
Abstract : A rare type of bezoar composed of coconut matting was found in the stomach of a caucasian man. The exact identity of the fibres was established by scanning electron microscopy, x-ray energy spectroscopy, and microscopic infrared spectroscopy. This report illustrates the importance of these techniques for identifying the nature of foreign material.